Onto the Farm, into the Home: How Intrahousehold Gender Dynamics Shape Land Restoration in Eastern Kenya - Crossland, M.; Paez Valencia, Ana Maria; Pagella, Tim; Magaju, C.; Kiura, E.; Winowiecki, Leigh Ann; Sinclair, Fergus L. (2021)
While attention has been paid largely to forest restoration, meeting global land restoration pledges will require scaling-up restoration of ecosystem services on agricultural land. This paper contributes to the literature on restoration practice and agricultural technology adoption, by shifting the focus onto the farm and considering the role of intrahousehold dynamics in the uptake of farmland restoration practices. We examine the intrahousehold decisions and gender relations surrounding the trial of two on-farm restoration practices: tree planting and planting basins; with over 2,500 farmers in the eastern drylands of Kenya. Combining results from household surveys, interviews and focus group discussions, our findings reveal that decisions over the uptake of restoration practices, although usually initiated by women who attend agricultural workshops, are often discussed between husband and wife and that multiple social dimensions intersect to shape men's and women's interest in, contribution to, and benefit from different practices. Furthermore, our study demonstrates that these intrahousehold relations are, in turn, shaped by women's participation in innovation processes and broader societal changes, particularly the outmigration of rural men. Based on these insights, we offer recommendations for improving the dissemination and uptake of on-farm restoration practices in eastern Kenya and achieving more inclusive and gender-equitable outcomes.